Lead and cadmium content in Nile tilapia (Oreochromis niloticus) from Egypt: A study for their molecular biomarkers - Alaa Eldin M.A. Morshdy; Wageh Sobhy Darwish; Mohamed A.M. Hussein; Mohamed Ali Abdrabo Mohamed; Mohamed M.A. Hussein (Scientific African, 2021)
This study was conducted to examine the residual levels of lead (Pb) and cadmium (Cd) in Nile tilapia (Oreochromis niloticus) collected from three locations (Abbassa, Damietta, and El-Husseiniya) in Egypt. Moreover, the effects of these heavy metals on the antioxidant status in fish were also studied. A trial was conducted to establish some molecular biomarkers reflecting the adverse biological responses towards heavy metals exposure in Nile tilapia by following up changes in the mRNA expression of metallothionein (MT) and heat shock protein (HSP70a). The obtained results indicated that both Pb and Cd residual levels in the fish muscles exceeded maximum permissible limits. Both gills and livers had higher levels of Pb and Cd compared with the muscular tissue. Contamination with heavy metals had a significant alteration on the antioxidant status in Nile tilapia. MT and HSP70a mRNA expressions in the livers of Nile tilapia collected from locations with high Pb and Cd contamination were significantly upregulated. The major novelty of the current study is studying the effects of Pb, and Cd on the antioxidant status in fish, and the development of two molecular biomarkers (MT and HSP70) for the Nile tilapia exposure to such pollutants that can be used as tools to understand the fish response and adaptation to the exposure to high levels of Pb, and Cd.